Declining blood lead levels among small-scale miners participating in a safer mining pilot programme in Nigeria. Issue 11 (5th September 2019) - Gottesfeld, Perry; Meltzer, Gabriella; Costello, Sadie; Greig, Jane; Thurtle, Natalie; Bil, Karla; Mwangombe, Benjamim Janeiro; Nota, Manti Michael
Abstract : Objectives: Our objective was to monitor blood lead levels (BLLs) of miners and ore processors participating in a pilot programme to reduce lead poisoning and take-home exposures from artisanal small-scale gold mining. A medical surveillance programme was established to assess exposures as new methods aimed at reducing lead exposures from ore were introduced in a community in Nigeria where children experienced substantial lead-related morbidity and mortality. Methods: Extensive outreach and education were offered to miners, and investments were made to adopt wet methods to reduce exposures during mining and processing. We conducted medical surveillance, including a physical exam and repeated blood lead testing, for 61 miners selected from among several hundred who participated in the safer mining pilot programme and consented to testing. Venous blood lead concentrations were analysed using the LeadCare II device at approximately 3-month intervals over a period of 19 months. Results: Overall geometric mean (GM) BLLs decreased by 32% from 31.6 to 21.5 µg/dL during the 19-month project. Women had a somewhat lower reduction in GM BLLs (23%) compared with men (36%). There was a statistically significant reduction in log BLLs from baseline to the final test taken by each participant (p<0.001). Conclusions: The observed reductions in GM BLLs during the pilot intervention among this representative group of miners and ore processors demonstrated the effectiveness of the safer mining programme in this community. Such measures are feasible, cost-effective and can greatly improve health outcomes in mining communities.